Emloyees’ Characteristics and Job Performance of Staff of the Bayelsa State Ministry of Education in Nigeria - Gede, Ngozi Tari; Lawanson, Olukemi Anike (Mediterranean Journal of Social Sciences, 2011)
The study investigated the relationship between employee characteristics and job performance in Bayelsa StateMinistry of Education. The characteristics under investigation were gender, age, educational level and experience. A descriptivedesign was adopted for the study. A sample size of 50 employees out of 221 members of staff representing 22.7% was randomlyselected for the study. A 14 item questionnaire titled “Employee Characteristics and Job Performance (ECJP) was developed tocollect data. The instrument was validated and a reliability coefficient of 0.79 was obtained using test-retest method. Fourhypotheses were used to guide the study and the null hypotheses were tested using the Chi-square statistical tool. The results ofthe study revealed that there existed a relationship between all the characteristics examined and job performance. It was thus,concluded that the poor performance of the staff of Ministry of Education could be attributed to employee characteristics. Thishas ultimately and adversely affected the teaching and learning in the state schools. The study thus, recommended among otherthings the recruitment of qualified personnel, and treating each individual distinctly to ensure high performance for theeducational development of the state.